North Korea's Response to US Army Propaganda Leaflets during the Korean War. (1st October 2016) - Kim, Eun-Jeong
Abstract : This study examines a particular aspect of the history of North and South Korea's bbira (propaganda leaflets), focusing on North Korea's propaganda strategies in response to US propaganda during the Korean War, including perceptions of propaganda leaflets targeting North Koreans and counterstrategies used against them. The research herein analyses Munhakyesul, the leaflets during the Korean War, and the leaflets held by the DMZ Museum. The findings of this study reveal characteristics of and differences between the psychological tactics used by North Korea and the US during the Korean War, as exhibited through the use of these propaganda leaflets.